2016
DOI: 10.1073/pnas.1518015113
|View full text |Cite
|
Sign up to set email alerts
|

Insurance coverage of customers induces dishonesty of sellers in markets for credence goods

Abstract: Honesty is a fundamental pillar for cooperation in human societies and thus for their economic welfare. However, humans do not always act in an honest way. Here, we examine how insurance coverage affects the degree of honesty in credence goods markets. Such markets are plagued by strong incentives for fraudulent behavior of sellers, resulting in estimated annual costs of billions of dollars to customers and the society as a whole. Prime examples of credence goods are all kinds of repair services, the provision… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 29 publications
0
33
2
1
Order By: Relevance
“…Our work provides further insight into previous research focusing on understanding the intrapersonal and interpersonal consequences of safety mechanisms (Gamble & Walker, ; Tykocinski, , ; Van de Calseyde, Keren, & Zeelenberg, ; Van Wolferen, Inbar, & Zeelenberg, ). For example, in demonstrating the consequences of insurance coverage in credence goods markets, Kerschbamer, Neururer, and Sutter () recently found that computer repair shops increased their bills with 80% when informed that insurance would reimburse the costs. In a similar vein, Walker () showed comparable interpersonal consequences (yet in a very different domain) as car drivers became less cautious in overtaking a cyclist when the cyclists wore a helmet.…”
Section: Discussionmentioning
confidence: 99%
“…Our work provides further insight into previous research focusing on understanding the intrapersonal and interpersonal consequences of safety mechanisms (Gamble & Walker, ; Tykocinski, , ; Van de Calseyde, Keren, & Zeelenberg, ; Van Wolferen, Inbar, & Zeelenberg, ). For example, in demonstrating the consequences of insurance coverage in credence goods markets, Kerschbamer, Neururer, and Sutter () recently found that computer repair shops increased their bills with 80% when informed that insurance would reimburse the costs. In a similar vein, Walker () showed comparable interpersonal consequences (yet in a very different domain) as car drivers became less cautious in overtaking a cyclist when the cyclists wore a helmet.…”
Section: Discussionmentioning
confidence: 99%
“…Falk and Szech [31] and Rothenhäusler et al [32] have studied morals in group voting. Kerschbamer et al [33], Bartling et al [34], and Friedrichsen and Engelmann [35] have considered ethical consumption and/or morally relevant credence goods. Our results indicate that consumers' moral excuses should receive specific attention in follow-up research.…”
Section: Introductionmentioning
confidence: 99%
“…Our main results fit consistently into the existing experimental literature on credence goods. The observation that physicians are heterogeneous in their response to overtreatment incentives has also been made in Beck, Kerschbamer, Qiu, and Sutter (2013); Dulleck et al (2011);Gottschalk et al (2017);and Kerschbamer et al (2016), with a particular discussion and estimation of heterogeneity in Kerschbamer et al (2017). Nevertheless, agents respond to incentives.…”
Section: Resultsmentioning
confidence: 99%